Effect of Construction Manager's Political Skills on Relationship between Quality Management Practices and Inter-Organizational Project Success - Ahsan Hussain Khan; Sepanta Naimi (Salehan Institute of Higher Education, 2024)
This study aims to explore the impact of construction managers' political skills on the relationship between quality management practices and the success of inter-organizational construction projects in Pakistan. Objectively, it examines how project managers' political acumen influences the effectiveness of quality management strategies and, consequently, project success. Employing a survey-based methodology, the research encompasses a broad spectrum of professionals involved in various construction projects across Pakistan. Through this analysis, the study identifies key challenges to project success and assesses the correlation between managerial political skills and the effective implementation of quality management practices. The findings reveal a notable positive relationship between these elements, highlighting the critical role of skills such as communication, stakeholder management, and conflict resolution. Additionally, the research underscores the interconnected nature of managerial competencies and identifies key factors impacting project success through advanced statistical techniques like principal component analysis and median absolute deviation. Significantly, this research provides novel insights into the role of human factors in the Pakistani construction industry's project management, proposing actionable strategies for skill enhancement and offering a comprehensive overview of factors influencing project success. These findings not only show the current skills and practices landscape but also lay the groundwork for future research and strategy implementation to boost industry-wide success. Doi: 10.28991/CEJ-2024-010-01-019 Full Text: PDF